Pinning down the problems and influences: Disordered eating and body satisfaction in male wrestlers - Satterfield, N. A.; Stutts, L. A. (Psychology of Sport and Exercise, 2021)
Objectives: Disordered eating and body dissatisfaction are common concerns among athletes. However, these variables have been minimally explored in male wrestlers. Sociocultural influences can impact drive for muscularity, body satisfaction, and disordered eating, but it is unclear which influences are most prominent in this population. The present study had two aims: 1) examine the nature of drive for muscularity, body satisfaction, and disordered eating in collegiate wrestlers, and 2) investigate which sociocultural influence (general, coach/teammate, sport appearance pressures) most strongly predicts drive for muscularity, body satisfaction, and disordered eating. Methods and design: This study was cross-sectional. Participants included 103 National Collegiate Athletic Association Division I male collegiate wrestlers in the U.S. who completed surveys in season on sociocultural influences, drive for muscularity, body satisfaction, and disordered eating. Results: Wrestlers had a high drive for muscularity and engaged in many unhealthy behaviors to lose weight; however, they had relatively high body satisfaction. Relative weight analyses showed that sport appearance pressures were the strongest predictor of drive for muscularity while general pressures were the strongest predictor of body satisfaction and restricting eating behaviors. Conclusions: Findings suggests that disordered eating needs to be addressed among wrestlers and potential influences to target.